Multilayer Sheets Based on Double Coatings of Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) on Paper Substrate for Sustainable Food Packaging Applications - Eva Hernández-García; Pedro A. V. Freitas; Pedro Zomeño; Chelo González-Martínez; Sergio Torres-Giner (Applied Sciences, 2022)
This work reports on the development and performance evaluation of newly developed paper sheets coated, on both sides, with thin films of biodegradable poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) for applications of food packaging. For this, PHBV/paper/PHBV multilayers were first prepared by the thermo-sealing technique, optimizing the process variables of temperature and time. Thereafter, the multilayer sheets were characterized in terms of their morphological, optical, thermal, mechanical, and barrier properties and compared with equivalent paper structures double coated with high-barrier multilayer films of petrochemical polymers. The results indicated that the double coatings of PHBV successfully improved the mechanical resistance and ductility, protected from moisture, and also reduced the aroma and oxygen permeances of paper, having a minimal effect on its optical and thermal properties. Finally, the compostability of the resultant multilayer sheets was analyzed, confirming that the presence of the PHBV coatings slightly delayed the aerobic biodegradation and disintegration of paper.